Edukasi Promosi Media Sosial Kuliner Makanan Dalam Penerapan Digitalisasi - Putra, Yogi; Elfitra Desy Surya; Furqan, Furqan (Jurnal Masyarakat Indonesia (Jumas), 2025)
Education and socialization Social media can play a role in developing and promoting culinary businesses that are mushrooming in Indonesia. Original Indonesian cuisine is very abundant and diverse and spread from Sabang to Merauke including seafood in Pari Serdang Bedagai City. Seafood cuisine in Pari Serdang Bedagai City has its own characteristics and represents the identity of each region in North Sumatra Province. By using social media to promote, of course it will be very helpful in showing culinary in Pari Serdang Bedagai City that is not yet widely known and without limits. Social media can be a platform that has the most potential to promote culinary in the future. Examples of social media that can be used to promote culinary businesses include Instagram, and Tiktok